1.RADIKALISASI GERAKAN PERLINDUNGAN BINATANG: SERANGAN ECO-TERORISME â€œOPERATION BITE BACKâ€ OLEH ANIMAL LIBERATION FRONT DI AMERIKA SERIKAT - Wahyudewi, Putri; Putranti, Ika Riswanti; Wahyudi, Fendy Eko (Journal of International Relations, 2016)
The vast growth of the environmentalist and animal rights movement during the 20thcentury has posed radicalization within it. Being labeled as the most active radical animalrights group in the United States, Animal Liberation Front (ALF) has emerged as the mostserious domestic terrorist threat in the country. In 1990, ALF created a series of attackscalled â€œOperation Bite Backâ€, through which it imposed threats and showed how this actof eco-terrorism is perpetrated. The purpose of this research is to give explanatory answerto why ALF chose the method of eco-terrorism in Operation Bite Back. By using ResourceMobilization theory, the result of this research is that the ALFâ€™s cell-formedorganizational structure and its leaderless resistance strategy give its members chances tobecome the key players and conduct their own attacks. In this case, Rod Coronado becamethe main variable of the eco-terrorist attacks. The analysis of this case has proven therationaliy of the actor in deciding the method and how internal and external factors areinterconnected and mobilized, making it highly significant to the formation of movements.